STRUCTURAL MODELS OF MILITARY DISCOURSE NEOLOGISMS IN LANGUAGE - Mammadjafarova Mehriban Isa (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
As in all languages, the Azerbaijani language is notable for its frequent changes at the lexical level. There are factors that affect each language primarily at the lexical level. Development in all areas of society leads to the emergence of new words and terms related to these areas. In our modern era, there is strong competition between states in the military field. The creation of new weapons by states to protect or defend their territorial integrity leads to an increase in the power of these states in the military-political field. With the production of self-defense and offensive weapons, their creation in accordance with modern standards, the lexicon of the language also changes and enriches accordingly. A military term is a word or a combination of words, used to indicate certain specific concepts and notions related to one or another branch of military science or military technology. As a result of the widespread spread of wars in the global world, the number of units expressing military concepts in the language increases in accordance with the development of that field, and thus rapid changes are observed in the military layer of the lexical layer of the language. This process of change observed in the lexical layer of the world's languages ​​is realized in different ways in different specific languages, in accordance with the internal laws of each language. The factors affecting these changes affect the development of military lexicon in different languages, and the achievements of society in this field are also reflected in its language. The use of semantic, morphological, syntactic and calculus methods in the language is realistic in the creation of military terms. The rapid development of science and technology has led to the creation of new terms in the military field. It is observed that words in the language acquire new meanings and multiply due to homonymy. A field term is a functional language element that manifests itself during specialized communication. A term is not a general attitude to life and its various fields, but rather the result of a scientific attitude, a professional-occupational attitude. The field lexical system is regulated by the existing laws of the national language. The military terminology system of the Azerbaijani language has played a major role in the enrichment of the general vocabulary. The oldest and most static way in the creation of military terms is considered to be the lexical way. In this way, the enrichment of the military lexicon differs fundamentally from the morphological and syntactic way. In addition, the enrichment of the military lexical fund has certain different characteristics from the enrichment of the general vocabulary of the national language.